От мифологии ландшафта к историографии страны - Саакян, Арцруни (Зангак-97)
In the article, the pre-Christian origins of the mythological figure of St. Nune/Nino are traced back to the story on a miraculous queen-fish drifting from Lake Parvana down-stream the Kura River. The ancient fish mythology, which is reflected in Nino’s name, was later awakened in Georgian Christian tradition. It is shown how the written and oral versions of Nino’s hagiography have preserved an almost classical example of transformation of a landscape mythology through monastic folklore into the official Church and even academic historiography of Georgia.
Keywords: Литература